Improving Dispersion and Barrier Properties of Polyketone/Graphene Nanoplatelet Composites via Noncovalent Functionalization Using Aminopyrene - Cho, Jaehyun; Jeon, Ikseong; Kim, Seong Yun; Lim, Soonho; Jho, Jae Young (American Chemical Society, 2017)
A series of polyketone (PK) nanocomposite films with varying content of noncovalently functionalized graphene nanoplatelet with 1-aminopyrene (GNP/APy) is prepared by solution blending with a solvent of hexafluoro-2-propanol. GNP/APy, prepared by a facile method, can effectively induce specific interaction such as hydrogen bonding between the amine functional group of GNP/APy and the carbonyl functional group of the PK matrix. With comparison of GNP and GNP/Py as reference materials, intensive investigation on filler matrix interaction is achieved. In addition, the dispersion state of the functionalized GNP (f-GNPs; GNP/Py and GNP/APy) in the PK matrix is analyzed by three-dimensional nondestructive X-ray microcomputed tomography, and the increased dispersion state of those fillers results in significant improvement in the water vapor y transmission rate (WVTR). The enhancement in WVTR of the PK/GNP/APy nanocomposite film at 1 wt % loading of filler leads to a barrier performance approximately 2 times larger compared to that of PK/GNP nanocomposite film and an approximately 92% reduction in WVTR compared to the case of pristine PK film. We expect that this facile method of graphene functionalization to enhance graphene dispersibility as well as interfacial interaction with the polymer matrix will be widely utilized to expand the potential of graphene materials to barrier film applications.
Keywords: GRAPHENE OXIDE; SHEETS; NANOCOMPOSITES; EXFOLIATION; INTERFACE; MECHANISM; STRENGTH